2015
DOI: 10.3844/jcssp.2015.89.97
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Anomaly Detection Using Data Mining Methods for Hypertext Transfer Protocol Web Services

Abstract: Abstract:In contrast to traditional Intrusion Detection Systems (IDSs), data mining anomaly detection methods/techniques has been widely used in the domain of network traffic data for intrusion detection and cyber threat. Data mining is widely recognized as popular and important intelligent and automatic tools to assist humans in big data security analysis and anomaly detection over IDSs. In this study we discuss our review in data mining anomaly detection methods for HTTP web services. Today, many online care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Supervised anomaly detection techniques detect anomaly based on generating a set of grouping rules that aid in predicting future data. An example of supervised anomaly detection is classification-based anomaly detection (Kakavand et al, 2015).…”
Section: Anomaly Detection Modesmentioning
confidence: 99%
See 3 more Smart Citations
“…Supervised anomaly detection techniques detect anomaly based on generating a set of grouping rules that aid in predicting future data. An example of supervised anomaly detection is classification-based anomaly detection (Kakavand et al, 2015).…”
Section: Anomaly Detection Modesmentioning
confidence: 99%
“…Semi-supervised anomaly detection is an approach that models only the normal records. The other records are labelled as outliers in the testing phase (Kakavand et al, 2015).…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations
“…Kakavand et al [3] provided an overview of data mining methods used by HTTP web services anomaly detection, concluding that most studies do not use public datasets that allow replication of the experiments. Those studies that do use public datasets showed high percentages of accuracy in most of the intrusion detection techniques employed, but these studies were not replicated with a different set of datasets.…”
mentioning
confidence: 99%